2020
DOI: 10.3390/app10196651
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of the Formation of Defects in Residential Buildings with Regards to Changes in Their Reliability

Abstract: Defining the basic determinants of the level of reliability with regards to the use of residential buildings and determining the function of the intensity of their characteristic defects are important issues concerning renovation strategy. The distribution of the exploitation time of residential buildings, the function of their reliability, and the distribution of the defect intensity of examined buildings are interdependent terms. Therefore, it can be assumed that the defect intensity of an object will be hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…As to assess the significance of the discrepancies between the values of the theoretical and observed technical wear distribution of elements of downtown residential buildings, two non-parametric tests with the ordinal measurement scale of variables—the Wilcoxon test and the Sign test—were used for two groups of independent data [ 40 , 41 ]. These tests also involve the proper ordering of ranks, dividing their sums into halves.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…As to assess the significance of the discrepancies between the values of the theoretical and observed technical wear distribution of elements of downtown residential buildings, two non-parametric tests with the ordinal measurement scale of variables—the Wilcoxon test and the Sign test—were used for two groups of independent data [ 40 , 41 ]. These tests also involve the proper ordering of ranks, dividing their sums into halves.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…The application of the original procedures of the intensification and dilution of membership functions, according to Formulas (12) and (13), to the general Formula (11) of the The final stage of the created model for assessing the technical wear (damage degree) of selected building elements in the three middle states of their technical maintenance is to estimate the size of the impact of elementary damage on the total damage. The study of the observed states and the conclusions from the proposed method of associating the occurring damage with the occurrence of the process of technical wear indicate a significant range of the strength of this relation within one building element in the maintenance states II, III and IV [1][2][3][4][5][6][7]. None of the values of the bi-serial correlation coefficient r(Z), which is a measure of this relationship, reaches a value of 1 in domain [0, 1].…”
Section: Appl Sci 2021 11 X For Peer Reviewmentioning
confidence: 99%
“…In practice, however, there are many cases in which the indeterminacy of the type of inaccuracy, ambiguity and imprecision of meanings can be found. However, these situations are not of a random nature, and therefore traditional probabilistic models may not be adequate [1][2][3][4][5][6][7]. When assessing the possibility of random and/or fuzzy events occurring in construction investment projects, apart from immeasurable (qualitative) criteria, measurable (quantitative) criteria are also used.…”
Section: Introduction 1source Literaturementioning
confidence: 99%
“…Authors Year Topic of Study Type of Approach [1][2][3][4] Zavadskas, Antuchevičienė, Kapliński, Konior 2007Konior -2015 Decision making Models and methods [5][6][7] Hellwig, Morrison, Jackson 2001 Randomness Statistics [8][9][10][11][12][13][14] Zadeh, Yager, Kaufmann, Sanchez, Kacprzyk 1965Kacprzyk -2007 Uncertainness Fuzzy sets [15][16][17][18] Knight, Menassa, Konior 2011-2020 Uncertainty Appraisal of buildings [19][20][21][22][23][24][25][26][27][28][29] Nowogońska, Konior…”
Section: Referencementioning
confidence: 99%
“…The problem of the damage and destruction of residential buildings is widely described in the literature [19][20][21][22][23][24][25][26][27][28][29]. There is even a classification of damage that is characteristic for different types of buildings [30][31][32][33][34][35][36][37][38], e.g., those erected using industrialized methods or those with traditional construction.…”
Section: Technical Damage and Wearmentioning
confidence: 99%